`c=sqrt(a^2+b^2)`

To solve for a, the square root must be eliminated. To do so, perform its opposite operation. So, square both sides of the equation.

`c^2=(sqrt(a^2+b^2))^2`

`c^2=a^2+b^2`

Next, move b^2 to the other side to have a^2 only at the right side. Again, do the opposite operation. Since the operation between a^2 and b^2 is addition, then subtract both sides by b^2.

`c^2-b^2=a^2+b^2-b^2`

`c^2-b^2=a^2`

And to have a only at the right side, its exponent 2 must be removed So, take the square root of both sides of the equation. And as per square root property, a has two values, the positive and negative. So,

`+-sqrt(c^2-b^2)=sqrt(a^2)`

`+-sqrt(c^2-b^2)=a`

Note that if **a** represents a dimension of a figure, take only the positive expression.

Since the problem does not indicate what **a** represents for, then consider the two expression of a.

**Hence, `a= +sqrt(c^2-b^2) ` and `a=-sqrt(c^2-b^2)` .**